Common words in Kazakh and Persian - Akhmetova F К; Gholamhosseinzadeh Г (Journal of Oriental Studies, 2016)
In this article, the authors examined the general words in Kazakh and Persian languages, and their history of origin. Are presented and examined some issues by borrowing. The article briefly describes some of the moments of the history of the development of relations in the past.